2015
DOI: 10.3389/fpsyg.2015.00066
|View full text |Cite
|
Sign up to set email alerts
|

Embodied intersubjective engagement in mother–infant tactile communication: a cross-cultural study of Japanese and Scottish mother–infant behaviors during infant pick-up

Abstract: This study examines the early development of cultural differences in a simple, embodied, and intersubjective engagement between mothers putting down, picking up, and carrying their infants between Japan and Scotland. Eleven Japanese and ten Scottish mothers with their 6- and then 9-month-old infants participated. Video and motion analyses were employed to measure motor patterns of the mothers’ approach to their infants, as well as their infants’ collaborative responses during put-down, pick-up, and carry phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…which directs collaborative action to make a new and valued reality for the 'cognitive consciousness' of a community (Panksepp and Biven, 2012). In concert with sociocultural theories (Vygotsky, 1978, Rogoff, 2003 we consider that such advances cannot be comprehended without consideration of their location within particular cultural practices and values (Negayama et al, 2015). The foundation for our knowledge is in our innate feelings for collaborative awareness in the experience of action (Delafield-Butt and Trevarthen, 2015).…”
Section: Story-telling From Birth: Making Sense Of Experience In Non-mentioning
confidence: 99%
“…which directs collaborative action to make a new and valued reality for the 'cognitive consciousness' of a community (Panksepp and Biven, 2012). In concert with sociocultural theories (Vygotsky, 1978, Rogoff, 2003 we consider that such advances cannot be comprehended without consideration of their location within particular cultural practices and values (Negayama et al, 2015). The foundation for our knowledge is in our innate feelings for collaborative awareness in the experience of action (Delafield-Butt and Trevarthen, 2015).…”
Section: Story-telling From Birth: Making Sense Of Experience In Non-mentioning
confidence: 99%
“…In many societies around the world the infant and mother are together after birth, swaddled, not nude and fathers are not involved in childbirth. 5 Taking cultural differences into account, continuous caring models involving skin-to-skin care immediately after birth should be seen as "good practice". 1,2,6,7,22 In a study by Velandia, et al 21 it was suggested that early mother-infant skin-toskin care immediately after caesarean section should be encouraged until the first breastfeed takes place.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The opportunity to hold the newborn infant immediately after birth is the pinnacle of the childbearing process. 3 Previous studies have shown the benefits of early parentinfant contact after birth, which include increased parental sensitivity to the infants signals and the way the newborn presents itself, 4,5 improved initiation of breastfeeding. 6,7 and calmer infant with improved pre-feeding behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In that framework, Negayama et al (2015) analyzed the intersubjective bodily involvement between adult and infant in daily actions in Scottish and Japanese mothers with their infants between six and nine months of age and found cultural differences in the intersubjective movement keys. In another framework, Brand, Baldwin and Ashburn (2002), Koterba andIverson (2009) andLicata et al (2014) found that, in their interactions with infants over eight months of age, the mothers modify and simplify their movements.…”
Section: The Resurgence Of the Study Of Movement In The 21st Centurymentioning
confidence: 99%
“…Given this trajectory, the contemporary investigation of movement is uprooted from its original proposals. There is a gap between the pioneering studies (Bateson, 1971;Beebe & Gertsman, 1980;Condon & Sander, 1974;Fogel, 1977;Stern, 1974aStern, , 1974bStern, Beebe, Jaffe, & Bennett, 1977) and contemporary research (Dissanayake, 2000;Fogel & Garvey, 2007;Malloch & Trevarthen, 2009;Negayama et al, 2015;Reddy, 2008;Thelen, 2000). Some current studies that analyze early interactive movement mention the pioneering studies as antecedents (Delafield-Butt & Trevarthen, 2013Gratier & Apter-Danon, 2009;Needham & Libertus, 2011), but there is a notable lack of systematics in the references and in the relations established between the theory and the former and current empirical data.…”
mentioning
confidence: 99%